Status prawny mniejszości narodowych i etnicznych w Polsce – ustawa o mniejszościach narodowych i etnicznych oraz języku regionalnym - Malicka, Agnieszka (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
Before 1989 and the transformation of the political and legal system took place, Poland was considered to be an ethnically homogenous country. At present, national minorities constitute according to statistical data, approximately 1% of the total population of Poland. The legal status of national and ethnic minorities is regulated in the Polish legal system in International Treaties of which Poland is part, the Constitution of the Republic of Poland, the Act on National and Ethnic Minorities and other provisions of general statutory law, not designed specifically to deal with minority issues.
Keywords: cultural and religious identity; minority culture preservation; educational and cultural institutions; electoral rights; discrimination